2004
DOI: 10.1016/j.femsre.2004.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Lipoproteins ofMycobacterium tuberculosis: an abundant and functionally diverse class of cell envelope components

Abstract: Mycobacterium tuberculosis remains the predominant bacterial scourge of mankind. Understanding of its biology and pathogenicity has been greatly advanced by the determination of whole genome sequences for this organism. Bacterial lipoproteins are a functionally diverse class of membrane-anchored proteins. The signal peptides of these proteins direct their export and post-translational lipid modification. These signal peptides are amenable to bioinformatic analysis, allowing the lipoproteins encoded in whole ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
180
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(185 citation statements)
references
References 134 publications
5
180
0
Order By: Relevance
“…In a second step, the signal peptidase, LspA, cleaves off the N-terminal signal peptide. Finally the acylated cysteine is additionally lipidated at its free amino group by the N-acyltransferase, Lnt (35). The triacylated N terminus anchors the mature lipoprotein to the bacterial cell membrane but can be further processed: for some lipoproteins, cleavage sites have been described that allow for an enzymatic shedding of the protein, which leaves the lipidated N terminus tethered to the cell membrane (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…In a second step, the signal peptidase, LspA, cleaves off the N-terminal signal peptide. Finally the acylated cysteine is additionally lipidated at its free amino group by the N-acyltransferase, Lnt (35). The triacylated N terminus anchors the mature lipoprotein to the bacterial cell membrane but can be further processed: for some lipoproteins, cleavage sites have been described that allow for an enzymatic shedding of the protein, which leaves the lipidated N terminus tethered to the cell membrane (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Lipoprotein functions in Gram-positive bacteria Bioinformatic analyses (as described earlier) have indicated that lipoproteins are a relatively abundant family of proteins, typically representing 2% or more of a Grampositive bacterial proteome [18,19,43,54,57]. Functional analyses have revealed several recognisable functional groupings of Gram-positive bacterial lipoproteins [3], with these functions reflecting the localisation of lipoproteins within the cell envelope and more specifically at the interface between the membrane and the cell wall (Box 3).…”
Section: Bioinformatic Prediction Of Lipoproteins In Grampositive Bacmentioning
confidence: 99%
“…Bioinformatic analysis indicates that Tat translocation of lipoproteins is widespread in the genus Streptomyces with up to 20% of putative lipoproteins being exported via Tat in the four currently sequenced Streptomyces species (M.I.H and I.C.S, unpublished). In comparison, $10%-15% of the putative lipoproteins of M. tuberculosis [18] are predicted to be Tat substrates, whereas only two of the 41 putative lipoproteins in the actinomycete Leifsonia xyli [19] are predicted to be Tat substrates (I.C. S, unpublished).…”
Section: Bacterial Lipoproteinsmentioning
confidence: 99%
See 2 more Smart Citations